2012
DOI: 10.1039/c2cc32313c
|View full text |Cite
|
Sign up to set email alerts
|

A gold nanocage–CNT hybrid for targeted imaging and photothermal destruction of cancer cells

Abstract: This communication reports the design of a novel aptamer conjugated gold nanocage decorated SWCNTs hybrid nanomaterial for targeted imaging and selective photothermal destruction of the prostate cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 24 publications
0
63
0
2
Order By: Relevance
“…7 The development of novel gold nanostructures and hybrids with a more efficient light-to-heat conversion is the other option. 27,28,30 The wrapping and embedding of gold nanostructures within graphene oxide (GO) and reduced graphene oxide (rGO) could be a way into this direction. [31][32][33] Kohane and coworkers showed that rGO coated gold nanoparticles kill cells more rapidly under 808 nm irradiation with a laser intensity of 3 W cm −2 , than did uncoated particles.…”
Section: Introductionmentioning
confidence: 99%
“…7 The development of novel gold nanostructures and hybrids with a more efficient light-to-heat conversion is the other option. 27,28,30 The wrapping and embedding of gold nanostructures within graphene oxide (GO) and reduced graphene oxide (rGO) could be a way into this direction. [31][32][33] Kohane and coworkers showed that rGO coated gold nanoparticles kill cells more rapidly under 808 nm irradiation with a laser intensity of 3 W cm −2 , than did uncoated particles.…”
Section: Introductionmentioning
confidence: 99%
“…197 In photo-triggered thermal activated drug release, low power densities e.g. 0.20 W cm −2 (Ag–Au shell–core), 160 0.6 W cm −2 (reduced GO), 198 and 1–2 W cm −2 (gold nanocage–CNT hybrid) 199 have been reported that do not damage tissue. Photo-triggered thermal systems have also led to a type of photochemotherapy with advantages including on-demand drug release, destruction of tumor cells either in light treated or light-shielded areas (the latter one due to heat-generated diffusing in the tissue), with a light-dosage dependent response.…”
Section: Different Stimuli-responsive Mnpsmentioning
confidence: 99%
“…SiO 2 @Au NPs were applied to optical imaging [229], biomedical detection [230], and photothermal cancer therapeutic ability [231], and may enable a new class of infrared materials, components, and devices to be developed. AuNCs and Au nanoframes were investigated in catalysis [232] and biosensing in view of their controllable LSPR properties that depend on the size and, most importantly, the thickness of the walls [233].…”
Section: Sensors and Molecular Recognitionmentioning
confidence: 99%